THE INFLUENCE OF DIGITAL MARKETING ON PURCHASING DECISIONS FOR SCARLETT WHITENING PRODUCTS (Case Study of Bengkalis State Polytechnic Students) - Fadhillah, Ulva; Hadi, Larbiel (Politeknik Negeri Bengkalis, 2024)
This research is an associative research that aims to analyze the effect of digital marketing implementation on purchasing decisions for Scarlett Whitening products. The problem in this study is the application of digital marketing and purchasing decisions made by consumers on Scarlett Whitening products. The sampling technique used Nonprobability Sampling technique. Respondents totaled 100 students who used Scarlett Whitening products at Politeknik Negeri Bengkalis and used primary data sources (questionnaires). The correlation coefficient is positive and unidirectional at 0.888. The simple linear regression equation which is positive at Y = 5.829 + 1.319X and the coefficient of determination shows 0.788, which means that digital marketing affects purchasing decisions by 78.8%. The T test results show that the t value of 19.100 is greater than the t table of 1.984, which means that H0 is rejected and Ha is accepted. This states that digital marketing variables influence purchasing decisions.Keywords: Digital Marketing, Purchasing Decisions, Scarlett Whitening products